2021
DOI: 10.1097/ncc.0000000000001010
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies for Stress and Self-Efficacy in Patients With Cancer and Their Spouses

Abstract: Stress coping strategiesBackground: Cancer is one of the most important diseases of the present century worldwide.Patients and their spouses can find more difficulty accepting the diagnosis of cancer than its phases of treatment. Both the physical health and mental health of the patient and spouse are important in the process of recovery from cancer and its treatment. Objective: The aim of this study was to determine the relationship between coping strategies for stress and self-efficacy in patients with cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…We also observed that a lower self-efficacy was associated with a higher cancer-specific distress. It is known that psychological interventions can improve patients’ self-efficacy and thus may reduce cancer-specific distress 28 29. However, we did not evaluate whether the patients received professional psychological support for their distress.…”
Section: Discussionmentioning
confidence: 98%
“…We also observed that a lower self-efficacy was associated with a higher cancer-specific distress. It is known that psychological interventions can improve patients’ self-efficacy and thus may reduce cancer-specific distress 28 29. However, we did not evaluate whether the patients received professional psychological support for their distress.…”
Section: Discussionmentioning
confidence: 98%
“…As breast cancer survivors experience less tension and discomfort, the negative feelings of the spousal caregiver decrease, prompting the spousal caregiver to better engage in home care, rather than focusing on cancer recurrence. The well-being of spousal caregivers improves the confidence of breast cancer survivors in overcoming the disease and their adherence to treatment and promotes recovery 39 40. Therefore, clinical practitioners should conduct family centred nursing interventions to alleviate spouses’ FCR, by reducing the perceived stress of breast cancer survivors to enhance family support, which could be regarded as a new approach to reduce survivors’ FCR.…”
Section: Discussionmentioning
confidence: 99%
“…17 Self-efficacy also relates to individuals' ability to control their behavior and coping strategies (ie, coping mode). 18 As an essential mechanism in the stress response, coping mode regulates and affects a person's responses to stress. When faced with stressful events, individuals may adopt different ways of relieving stress, affecting their QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy also relates to individuals’ ability to control their behavior and coping strategies (ie, coping mode) 18 . As an essential mechanism in the stress response, coping mode regulates and affects a person’s responses to stress.…”
Section: Introductionmentioning
confidence: 99%